Coping Strategies among Caregivers of Children with Acute Leukemia at Nanakali Hospital in Erbil City - Sinur Askander Hamad; Norhan Zeki Shaker (Hawler Medical University, 2019)
Background and objective: Childhood with leukemia is one of the developing global health issues, which has negative psychological, social, and physical consequences on care-givers, and affects the quality of long-term care of leukemic children. The current study aimed to assess coping strategies among caregivers of children with acute leukemia in Erbil City in the Kurdistan Region of Iraq. Methods: A descriptive study was carried out at the Nanakali Hospital for Blood Diseases and cancer in Erbil City from 10th October 2018 to 10th June 2019. The research sample involved 54 caregivers of leukemic children undergoing chemotherapy that were purposively recruited for the study. The researchers used a standard tool of "Coping Health Inventory for Parents" after verifying its validity and reliability. The data were collected by interviewing the participants and analyzed using frequency, percentage, mean, chi-square, and Fisher's exact test. Results: More than half, 28 (52%) of the children were female and the majority, 48 (88.9%) of them were diagnosed with acute lymphoblastic leukemia. The mean age of caregivers was 36.53± 7.53 years, and the majority of chief caregivers (87%) were mothers, mainly illiterate and secondary school graduates. Regarding the overall levels of coping patterns scores among caregivers, the highest percentage (61.1%) of them were at the medium level. Concerning each of the three levels of coping patterns score; for 87% of care-givers, maintaining family integration was within the medium level, while social support and self-esteem and an understanding medical situation, had lower percentages of 59.3% and 63% retrospectively. The results of the study revealed that there is a significant relationship between levels of coping and caregiver's education. Conclusion: According to the findings of the study, the majority of caregivers of children with leukemia undergoing chemotherapy treatment had a low level of coping in most of the coping patterns domains.